Conflict Management in Education: Theological, Philosophical and Theoretical Perspectives - Bambang Yasmadi; Sobari Sobari; Nandang Koswara; Faiz Karim F (Institute of Computer Science (IOCS), 2021)
Conflict in educational organizations is an unavoidable dynamic along with the growth and development of the organization. Conflicts arise as differences in interests between various parties, both the organizing body, the implementing agency and the students themselves as a result of competition, differences in socio-economic backgrounds, ethnic differences, individual characteristics and various other differences. To a certain extent, in order for the organization to run dynamically, conflict also needs to be created. In order to control conflict so that it has a positive impact on organizational growth, proper conflict management is needed. In this paper, a study of conflict management is carried out in theological, philosophical and theoretical perspectives to produce an appropriate conflict management formulation for the world of education. Theologically, it is stated in Islam that humans are basically created differently, in tribes and nations to know each other. The highest rank in front of Allah SWT are those who believe the most. In addition, Islam stipulates that conflict resolution must be based on the principles of justice, mercy (compassion) and collaboration. Philosophically, in the perspective of existentialism philosophy, conflict is a clash of individuals or groups in the context of self-existence. So that each existence does not nullify each other, arrangements are needed based on the principles of the existence of each individual/group, togetherness and justice. Whereas theoretically, in Dahrendorf's perspective, conflict is an unavoidable symptom in social groups, so that in its solution a coercive instrument is needed in the form of domination and elements of power. Based on the three perspectives above, conflict management in the world of education should be designed in such a way as to create dynamics that allow each individual/group involved to increase their capacity and existence in order to become knowledgeable and pious people. Conflict management must also uphold the spirit of justice, mercy, fair competition, dialogue, negotiation and collaboration between individuals/groups which in its implementation requires coercive regulations that are mutually agreed upon by each element in the organization.